2015
DOI: 10.1111/cei.12648
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the beneficial immunomodulatory mechanism of the sevoflurane metabolite hexafluoro-2-propanol in a rat model of endotoxaemia

Abstract: SummaryVolatile anaesthetics such as sevoflurane attenuate inflammatory processes, thereby impacting patient outcome significantly. Their inhalative administration is, however, strictly limited to controlled environments such as operating theatres, and thus an intravenously injectable immunomodulatory drug would offer distinct advantages. As protective effects of volatile anaesthetics have been associated with the presence of trifluorinated carbon groups in their basic structure, in this study we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 41 publications
(59 reference statements)
1
18
0
1
Order By: Relevance
“…This is thought to be due to an altered immune response which reduces the damaging inflammatory response in such situations. 81 Early work by Urner showed that the immunomodulatory effects of volatile anaesthetics are due to the presence of fluorinated carbon groups 82 and subsequently, Herrmann and coworkers postulated that HFIP could elicit a similar immunomodulatory response. Intraveneous administration of HFIP was shown to significantly improve survival rate in murine models of cecal ligation and puncture.…”
Section: Chemistry and Biology A) Hfip: A Primary Metabolite Of Sevofmentioning
confidence: 99%
See 1 more Smart Citation
“…This is thought to be due to an altered immune response which reduces the damaging inflammatory response in such situations. 81 Early work by Urner showed that the immunomodulatory effects of volatile anaesthetics are due to the presence of fluorinated carbon groups 82 and subsequently, Herrmann and coworkers postulated that HFIP could elicit a similar immunomodulatory response. Intraveneous administration of HFIP was shown to significantly improve survival rate in murine models of cecal ligation and puncture.…”
Section: Chemistry and Biology A) Hfip: A Primary Metabolite Of Sevofmentioning
confidence: 99%
“…Intraveneous administration of HFIP was shown to significantly improve survival rate in murine models of cecal ligation and puncture. 81 The most recent work demonstrates the effect of intraveneous HFIP administration in attenuating inflammation in rats, and found it to be equal, and in some measures superior, to inhaled sevoflurane. 82 This effect was attributed to reduced levels of proinflammatory mediators in plasma and tissue which leads to decreased white blood cell (neutrophil) invasion at the site of injury, hence attenuating apoptosis in internal organs.…”
Section: Chemistry and Biology A) Hfip: A Primary Metabolite Of Sevofmentioning
confidence: 99%
“…Reverse transcription and real-time quantitative PCR for CINC-1, MCP-1, IL-6, intercellular adhesion molecule-1 (ICAM-1) and TGFb1 were performed as previously described. 28 Details of forward and reverse primers as well as the probes used can be found in Table 1.…”
Section: Real-time Pcr Analysis Of Inflammatory Markers In Brain Tissuementioning
confidence: 99%
“…No toxicity for HFIP at clinically derived concentrations has been reported to date. Besides, HFIP suppresses endotoxin-stimulated inflammatory mediator secretion and improves the survival rate of septic peritonitis mice models [ 20 ]. Fluorinated alcohols, such as HFIP, have a particularly strong protein-denaturing activity and break the β-sheet structure leading to α-helix.…”
Section: Introductionmentioning
confidence: 99%